Picture and Picture Visual Learning for Improving Economics Achievement: Evidence from a Pre-Experimental Classroom Study - Nur Haliza; Muhammad Yany; Sandi (EduLine: Journal of Education and Learning Innovation, 2026)
The low level of student engagement in Economics learning, which remains predominantly teacher-centered, may negatively affect learning outcomes. One alternative to improve students' participation and academic achievement is the implementation of the Picture and Picture learning model, which utilizes visual media to facilitate the learning process. This study aimed to examine the effect of the Picture and Picture learning model on students' learning outcomes in Economics at the tenth grade of SMA Negeri 15 Bone. This research employed a quantitative approach using a pre-experimental design with a One-Group Pretest–Posttest Design. The sample consisted of 34 students from class X.G selected through random sampling. Data were collected using a learning achievement test and a student response questionnaire and were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test because the data were not normally distributed. The results indicated that the implementation of the Picture and Picture learning model improved students' learning outcomes, as reflected in the increase in the mean score from 49.81 on the pretest to 87.84 on the Posttest. Furthermore, the Wilcoxon Signed Rank Test revealed a significance value of p < 0.05, indicating a statistically significant effect of the Picture and Picture learning model on students' learning outcomes. In addition, most students expressed positive responses toward the implementation of the learning model. Therefore, the Picture and Picture learning model can be considered an effective instructional alternative for improving students' learning outcomes in Economics.